Signifikansi Berpikir Kreatif dan Motivasi Berprestasi dalam Kewirausahaan Serta Relevansinya dengan Pendidikan Islam - Samriana; Saputri, Andi Aprilia; Chairunnisa, Vina Oktavia; Maryati, Sulis (Cahaya Ilmu Bangsa Institute, 2024)
Creative thinking is a process used when an individual comes up with a new idea. The purpose of writing this article is to formulate Creative Thinking and Achievement Motivation; Creative Thinking and Achievement Motivation in Entrepreneurship; and the Relevance of Creative Thinking and Achievement Motivation in Islamic Education. The results of this writing are Creative thinking is a process used when an individual brings or brings up a new idea; The role of creative thinking in entrepreneurship is not only about generating new ideas, but also about implementing those ideas effectively in a business context; Islamic education is the process of forming individuals based on Islamic teachings to achieve high degrees so that they are able to fulfill their function as caliphs on earth and succeed in realizing happiness in this world and the hereafter.